Health Benefits of Zumba Fitness Training: A Systematic Review. Issue 12 (16th June 2016) - Vendramin, Barbara; Bergamin, Marco; Gobbo, Stefano; Cugusi, Lucia; Duregon, Federica; Bullo, Valentina; Zaccaria, Marco; Neunhaeuserer, Daniel; Ermolao, Andrea
Abstract: Objective: As an alternative to the traditional approach to physical exercise, new kinds of organized physical activity have been developed designed to engage large segments of the population. Among these, Zumba fitness is extremely popular, with a growing number of participants. This article aims to summarize and analyze the body of evidence on the effects of Zumba fitness interventions on physical function, fitness, and wellbeing. Type: Systematic review. Literature Survey: Keyword "Zumba" was identified as term for the literature research in MEDLINE, Scopus, Bandolier, PEDro, and Web of Science. Only studies published in peer‐reviewed journals written in English language were considered. Methodology: Eleven manuscripts were classified as eligible with 586 total participants, ranging in age from 18 to 65 years. After a quality appraisal, we classified 4 studies as high‐quality investigations and 7 as low quality. Results were summarized in several domains: "anthropometric parameters and body composition, " "hormonal and metabolic profiles, " "aerobic and cardiovascular performance, " "muscular fitness parameters, " and "quality of life, pain score and physical activity questionnaire." Synthesis: Results from this systematic review indicated that Zumba fitness could be considered an effective type of physical activity able to improve aerobic capacity. Small but positive benefits were noted for reducing body weight and other body measurements. Furthermore, other effects, including psychological and social benefits on quality of life, were found after Zumba fitness interventions. Otherwise, limited evidence described positive effects on muscular strength and flexibility. Conclusions: Zumba fitness could be considered an effective type of physical activity able to improve aerobic capacity. Limited evidence described positive effects on muscular strength and flexibility. Level of Evidence: II